2013
DOI: 10.1177/2151458513484759
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of a Geriatric Hip Fracture Clinical Pathway in Reducing Hospital and Rehabilitation Length of Stay and Improving Short-Term Mortality Rates

Abstract: Background: A geriatric hip fracture clinical pathway, led by an orthopedic surgeon, was developed in 2007. This clinical pathway team is multidisciplinary and consists of surgeons, physicians, anesthetists, nurses, physiotherapists, occupational therapists, medical social workers, dieticians as well as voluntary support groups. Methods: From early 2007 onward, all patients older than 65 years with acute isolated hip fractures were included. During the whole inpatient treatment, all relevant data were captured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
49
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 17 publications
4
49
1
3
Order By: Relevance
“…10 There were 1257 (46.6%) femoral neck fractures, 1445 (49.6%) intertrochanteric fractures, and 110 (3.8%) subtrochanteric fractures, comparable with a previous local study of 1342 hip fracture patients from 2007 to 2010. 8 The majority of patients had an ASA score of 2 and 3, comprising 40.9% and 56.3%, respectively and in line with Lau et al's study. 8 There was a marked increase in hemiarthroplasties and intramedullary fixations with 977 (33.5%) and 983 (3.7%) cases respectively in our study, compared with Lau et al's study that reported 362 (27%) hemiarthroplasties and 218 (16%) cephalomedullary nail fixations.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…10 There were 1257 (46.6%) femoral neck fractures, 1445 (49.6%) intertrochanteric fractures, and 110 (3.8%) subtrochanteric fractures, comparable with a previous local study of 1342 hip fracture patients from 2007 to 2010. 8 The majority of patients had an ASA score of 2 and 3, comprising 40.9% and 56.3%, respectively and in line with Lau et al's study. 8 There was a marked increase in hemiarthroplasties and intramedullary fixations with 977 (33.5%) and 983 (3.7%) cases respectively in our study, compared with Lau et al's study that reported 362 (27%) hemiarthroplasties and 218 (16%) cephalomedullary nail fixations.…”
Section: Discussionsupporting
confidence: 75%
“…8 The majority of patients had an ASA score of 2 and 3, comprising 40.9% and 56.3%, respectively and in line with Lau et al's study. 8 There was a marked increase in hemiarthroplasties and intramedullary fixations with 977 (33.5%) and 983 (3.7%) cases respectively in our study, compared with Lau et al's study that reported 362 (27%) hemiarthroplasties and 218 (16%) cephalomedullary nail fixations. 8 This reflects a change in the surgical treatment, possibly due to a lower re-operation rate, 11 better functional outcomes, 12 and higher cost-effectiveness 13 in patients treated with hemiarthroplasty; and minimal rate of fixation failure, less blood loss, and shorter length of hospital stay in patients treated with intramedullary fixation.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Literature on effects of clinical pathways for hip fractures generally shows positive results, although some publication bias cannot be excluded [10][11][12][13]. A recent review by Leigheb et al showed similar reductions in the hospital length of stay in eight out of 12 studies [6].…”
Section: Discussionmentioning
confidence: 97%